Citrus tristeza virus (CTV) in Cyprus, 1992-2004 - Kyriakou A.; Kapari T.I.; Gavriel I.; Papayiannis L.; Ioannou N. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
A historical review of CTV in Cyprus is presented with special reference to the epidemics that occurred in the period from 1992 to 2004. Monitoring was based on ELISA assays and the whole groves were eradicated when CTV incidence was equal to or lower than 15 percent. The general CTV infection rate equaled 4.43 percent; CTV biological and molecular characterization highlighted the south-African origin of the isolates which were introduced in the district of Ammockostos. A law was issued to prohibit the movement of citrus planting from this district to other areas. Ortanique and the red-flesh grapefruits were the most infected. The presence of CTV was the main driving force for the elaboration and implementation of a citrus certification programme in the 1990's.